2019
DOI: 10.9734/jamps/2019/v21i130120
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Postero-anterior Chest Radiographs Seen in a North-west Nigerian Tertiary Hospital

Abstract: Objectives: To determine the quality of chest radiographs of adult patients x-rayed at Usmanu Danfodiyo University Teaching Hospital (UDUTH) in accordance with Committee of European Commission (CEC) guidelines on quality criteria and to determine the most common factor that affects the radiographs. Materials and Methods: The data was collected retrospectively from the hospital archives using a data capture sheet. Results: A total of 266 radiographs were assessed and the age of patients whose radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
1
2
1
Order By: Relevance
“…All the parameters, except the adequate positioning of scapula out of the lung fields, were less in their study as compared to the present study.Radiographic images of poor diagnostic quality result in repeats and hence more radiation dose to the patients and economic loss to the hospital. The overall quality of chest radiographs was met in only 22.22% of the chest radiographs, similar to in a study done by Okeji et al and Abubakar et al, which is alarming 2,8. This indicates the need for improvisation of the techniques of obtaining chest radiographs.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…All the parameters, except the adequate positioning of scapula out of the lung fields, were less in their study as compared to the present study.Radiographic images of poor diagnostic quality result in repeats and hence more radiation dose to the patients and economic loss to the hospital. The overall quality of chest radiographs was met in only 22.22% of the chest radiographs, similar to in a study done by Okeji et al and Abubakar et al, which is alarming 2,8. This indicates the need for improvisation of the techniques of obtaining chest radiographs.…”
supporting
confidence: 74%
“…The current study even showed a statistically significant association of age with the scapula out of lung fields. The overall image quality of chest radiographs was poor in the study done by Abubakar et al as compared to the present study 8. All the parameters, except the adequate positioning of scapula out of the lung fields, were less in their study as compared to the present study.Radiographic images of poor diagnostic quality result in repeats and hence more radiation dose to the patients and economic loss to the hospital.…”
contrasting
confidence: 72%
See 2 more Smart Citations